1999
DOI: 10.1007/bf03165420
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Tc-99m ECD in delayed SPECT of the brain

Abstract: We determined the effect of retention on the changes in regional biodistribution of Tc-99m ECD in the brain. A total of 14 cases, 7 normal volunteers and 7 patients with various diagnoses but with very minimal radiologic findings or none were included in the study. SPECT images were taken at 30 min, 1, 2, 3, 4 and 6 hrs after an intravenous injection. Retention rates were calculated in various regions and were corrected according to the time decay of technetium. There was a tendency for the retention rate to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…There is one in vitro study supporting the hypothesis that esterase activity is the major determinant of the overall retention of ECD (Jacquier-Sarlin, Polla, & Slosman, 1996). Evidence about regional variation for clearance of [ 99m Tc]Tc-ECD in normal brain are controversial (Flores et al, 1999;Ichise et al, 1997;Leveille et al, 1989). In a study of epilepsy, [ 99m Tc]Tc-ECD washout rate was reported to be slightly lower but statistically signi cant in the hyperperfused areas than in other brain areas.…”
Section: Introductionmentioning
confidence: 99%
“…There is one in vitro study supporting the hypothesis that esterase activity is the major determinant of the overall retention of ECD (Jacquier-Sarlin, Polla, & Slosman, 1996). Evidence about regional variation for clearance of [ 99m Tc]Tc-ECD in normal brain are controversial (Flores et al, 1999;Ichise et al, 1997;Leveille et al, 1989). In a study of epilepsy, [ 99m Tc]Tc-ECD washout rate was reported to be slightly lower but statistically signi cant in the hyperperfused areas than in other brain areas.…”
Section: Introductionmentioning
confidence: 99%
“…The correction for the relative 99m Tc-ECD clearance described by Ichise et al [16] was calculated in a sample of 20 healthy volunteers with a mean age of 35±10 years, employing anatomically standardised subject data, an ROI analysis and curve fitting techniques. On the other hand, Flores et al investigated this matter in seven volunteers and seven patients, with manual redrawing of the ROIs on each image [21]. Overall, significantly lower washout values were obtained, while the relative thalamic uptake was even reported to increase with time.…”
Section: Discussionmentioning
confidence: 91%
“…Radiochemical purity (RCP) of Tc-99m-ECD is used for the quality control (QC) purpose [14–16]. Although the characteristics of Tc-99m-ECD, such as in vivo kinetics and biodistribution studies in healthy human [15, 17], pharmacological studies in primates [14, 18], uptake, clearance, and brain retention [1922], biotransformation, metabolites, and stability [14, 21, 23], have been well-investigated, the chemical properties (such as purity and content) of ECD in ECD Kit (Vial A), that is, API in drug product, which might significantly disqualify the efficacy of Tc-99m-ECD have not been much discussed. Moreover, no analytical method for the determination of content and uniformity of ECD in ECD Kit has been published.…”
Section: Introductionmentioning
confidence: 99%